Impact of Ageing on Serum Concentrations of Risperidone and Its Active Metabolite in Patients with Known CYP2D6 Genotype. Issue 5 (31st May 2016) - Molden, Espen; Waade, Ragnhild Birkeland; Hoff, Maren; Haslemo, Tore
Abstract: The aim of this study was to investigate the impact of ageing on serum concentrations of risperidone and 9‐hydroxyrisperidone in patients with known CYP2D6 genotype. We included retrospective therapeutic drug monitoring data from 464 genotyped patients with measured serum concentrations of risperidone and 9‐hydroxyrisperidone after oral administration. Patients were divided into two age subgroups, that is ≤65 (n = 396) and >65 years (n = 68), and dose‐adjusted concentrations (C:D ratios) were compared using multiple linear regression analyses with CYP2D6 genotype and gender as covariates. Moreover, absolute concentrations and prescribed daily doses were compared between age subgroups by simple, univariate Mann–Whitney tests. Age had no effect on C:D ratio of risperidone ( p > 0.4), but C:D ratios of 9‐hydroxyrisperidone and risperidone + 9‐hydroxyrisperidone (total active moiety) were estimated to be 2.6 and 2.0 times higher in patients >65 versus ≤65 years ( p < 0.001). Female gender and a CYP2D6 poor metabolizer (PM) genotype were also associated with significantly higher C:D ratio of the total active moiety ( p < 0.01). Despite lower dosing in patients >65 versus ≤65 years (median 1.5 versus 3.0 mg/day, p < 0.0001), absolute concentration of the total active moiety did not differ between the age subgroups (median 52.5 versus 47.0 nmol/L, p > 0.6). In conclusion, ageing implies significantly increased dose‐adjusted serum concentration of risperidone active moiety, and treatment intensity is not generally reduced by halving the oral dose in the elderly. Tolerability of risperidone therapy should therefore be closely monitored in older patients, and female CYP2D6 PMs >65 years might be a particularly vulnerable subgroup of adverse effects.